sec-Butylpropylacetamide (SPD), a New Amide Derivative of Valproic Acid for the Treatment of Neuropathic and Inflammatory Pain - Kaufmann, Dan (Pharmacol Res, 2016)
Chronic pain is a multifactorial disease comprised of both inflammatory and neuropathic components that affect ~20% of the world’s population. sec-Butylpropylacetamide (SPD) is a novel amide analogue of valproic acid (VPA) previously shown to possess a broad spectrum of anticonvulsant activity. In this study we defined the pharmacokinetic parameters of SPD in rat and mouse, and then evaluated its antinociceptive potential in neuropathic and acute inflammatory pain models. In the sciatic nerve ligation (SNL) model of neuropathic pain, SPD was equipotent to gabapentin and more potent than its parent compound VPA. SPD also showed either higher or equal potency to VPA in the formalin, carrageenan and writhing tests of inflammatory pain. SPD showed no effects on compound action potential properties in a sciatic nerve preparation, suggesting that its mechanism of action is distinct from local anesthetics and membrane stabilizing drugs. SPD’s activity in both neuropathic and inflammatory pain warrants its development as a potential broad-spectrum anti-nociceptive drug.